Edukasi & Pendampingan Pengelolaan Keuangan Keluarga Sebagai Upaya Menigkatkan Kesejahteraan Rumah Tangga di Kelurahan Sari Rejo Medan - Dina Rosmaneliana; Renny Lubis; Susan Novrini; Jamaluddin Jamaluddin (Universitas Methodist Indonesia, 2026)
Good family financial management is a crucial factor in improving household well-being. However, many people lack adequate financial literacy, often experiencing difficulty effectively managing income and expenses. This can lead to family economic instability, low savings rates, increased consumer behavior, and a lack of preparedness for urgent needs and future planning. This lack of understanding of financial management prevents people from optimally utilizing their income to improve their family's quality of life. This community service activity aims to provide education and guidance on family financial management to the community in Sari Rejo Village. The methods used in this activity include counseling, training, discussions, and direct assistance in preparing a simple and applicable household budget. The material provided covers financial planning, expense management, financial recording, controlling consumer spending, and the importance of simple savings and investments. The results of the activity indicate an increase in community understanding of the basic concepts of financial literacy and family financial management practices. Participants are beginning to be able to distinguish between needs and wants, allocate income more wisely, and prepare a family financial budget. In addition, there have been positive changes in financial behavior, such as the habit of saving regularly and recording daily expenses. This program is expected to improve household welfare and encourage sustainable financial independence in the community.